Morphometric Study of Endosteal Diameter of the Surgical Neck of Humerus through Digital Radiographic Analysis - Alam, Md Towhidul; Kishwara, Segupta; Kamal, A H M Mostafa; Sultana, Abeda; Faysal, Tanvir; Yasmin, Fahmida; Das, Sanchita Rani; Munmun, Rydwana (Community Based Medical Journal, 2025)
Endosteal diameter at the surgical neck of the humerus is a very important parameter in shoulder arthroplasty in terms of designing its prosthesis. A cross-sectional, analytical study was carried out in the Department of Anatomy, Dhaka Medical College, Bangladesh, from January to December of 2019, to observe the gender variation of the endosteal diameter of the surgical neck of the humerus in the adult Bangladeshi population through digital radiographic analysis. This study was performed by analyzing digital radiographs of left shoulder joint of 100 subjects (50 male and 50 female) attending the Radiology & Imaging of the same institution (aged between 26 and 49 years). They were selected based on our inclusion and exclusion criteria by adopting convenient purposive sampling method. After taking digital x-ray, those images were transferred to a computer. Diameter from those radiographs were then measured by using computer software named ‘MB-Ruler’. The mean endosteal diameters of the surgical neck of the humerus among Bangladeshi male and female were found 18.21±2.25 mm and 15.07±2.20 mm respectively. The range of the endosteal diameter at the surgical neck of the humerus was from 14.29 mm to 26.83 mm in male and from 8.94 mm to 19.35 mm in female. The mean value was higher in male comparing to its female counterpart (p<0.001). CBMJ 2025 July: vol. 14 no. 02 P:76-80